A Study of Thermal Comfort in Classroom Under Natural Ventilation and Air-Conditioner Condition in Hot and Humid Climate Country - Shahrom, Farah Arisha; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2021)
Thermal comfort significantly affects the productivity and satisfaction of classroom occupants. A comfortable learning environment should be provided as it affects the teaching and learning process of students. Thermal system must be improve to increase the minimum level and evaluate the most suitable of comfort for students and lecturers in the classroom. This paper reviews study on the thermal environment of classroom under natural and air conditioner condition in hot and humid climate.The main objective is to identify thermal comfort range for classroom by natural and air-condiioned means in hot and humid climate. The data colletion involve two main phases where the first phase is by systematic review for both survey and field measurement types of studies. While the second phase focused on data abstraction and analysis. The result shows that majority respondent in the studies prefer 24°C to 26°C environment condition which is within the recommended temperature by ASHRAE Thermal Comfort Standard. Some students could have higher heat tolerances (27°C to 28°C) in the air-conditioned classrooms as they may accept heat levels that exceeded the standard although, there were about 17% students who preferred in cooler environments (21°C to 23°C) and more sensitive to warm conditions. Meanwhile, in the natural ventilation classroom, it seems that the range of temperature acceptable (23°C to 30.9°C). As conclusions, an adaptive thermal comfort strategies were identified as strategies to adjust the comfortable temperature ranges under air-conditioning system and natural ventilation condition for energy saving in classrooms.